Evolution of PEKK crystallization measured in laser sintering - Benedetti, L.; Brulé, B.; Decraemer, N.; Evans, K. E.; Ghita, O. (Frontiers in Manufacturing Technology, 2022)
The rising popularity of laser sintering (LS) technology has increased by the broadening of available materials for this process. Kepstan 6002 poly (ether ketone ketone) (PEKK) was recently launched as a high-performance polymer grade with a lower processing temperature and unique crystallization kinetics. This study aims to understand the progress of crystallization on samples manufactured throughout the laser sintering process. These results were compared with isothermal and dynamic differential scanning calorimetry (DSC) experiments with different cooling rates. Kepstan 6002 PEKK processed by high-temperature laser sintering (HT-LS) presents a kinetics of crystallization in the order of ∼10 times slower than its crystallized samples in the DSC. This result highlights the need for a part-based crystallization investigation rather than isothermal models to describe the crystallization in LS. The transmission electron microscopy (TEM) analysis reveals smaller spherulites in the samples subjected to prolonged cooling times and an almost amorphous structure for the PEKK samples exposed to almost no cooling. This experiment identified the surroundings of laser sintered particles as preferential sites for crystallization initiation, which grows as the particles penetrate the molten layers and spherulites are formed. The slower kinetics of crystallization of Kepstan 6002 PEKK grade improve the adhesion between layers in laser sintering and enable tailoring its properties according to the application. Understanding the relationship between intrinsic material characteristics and the resulting final properties is vital to optimizing the process and controlling the final performance of PEKK for different applications.